The War on Terror in comparative perspective US security and foreign policy after 9/11 - Miller, Mark J.; Stefanova, Boyka 1960- (Palgrave Mcmillan, 2007)
This book offers a thoughtful analysis of the international and domestic political impact of the global war on terrorism through the prism of US security relations in the wake of September 11, 2001. While focused on regional and country-specific responses and consequences, the book redresses the balance between change and continuity in the international system brought about by the war on terror. The unusual meshing of wide-ranging views and perspectives represents the shared wisdom of an epistemic community emerging at the intersection of international relations, comparative politics and foreign policy analysis.